Levels of the Candida metabolite D-arabinitol in sera of steroid-treated and untreated patients with sarcoidosis. - Wong, B (1989)
We measured the Candida metabolite D-arabinitol and its enantiomer L-arabinitol in 42 serum samples from 33 patients with sarcoidosis and compared the results with those from 27 healthy adults and 4 patients with candidiasis. The D- and L-arabinitol concentrations and the D- and L-arabinitol/creatinine ratios did not differ significantly in the sarcoidosis patients and the controls; the D-arabinitol concentrations and the D-arabinitol/creatinine ratios were much higher in the patients with candidiasis. Among the patients with sarcoidosis, the D- and L-arabinitol levels in the steroid recipients did not differ significantly from those in patients not receiving steroids. Higher D-arabinitol/creatinine ratios were associated with roentgenographic evidence of pulmonary fibrosis and low forced vital capacities, but not with disease activity as determined by the proportion of lymphocytes to total nucleated cells in bronchoalveolar lavage fluid or the CD4/CD8 ratio in bronchoalveolar lymphocytes. We conclude that neither sarcoidosis nor corticosteroid treatment is associated with high levels of D-arabinitol in serum.